Developing contextual-based BIPA teaching materials integrating muhammadiyah values to enhance learners’ communicative competence - Khaerunnisa Khaerunnisa; Mutiarani Mutiarani; Wika Soviana Devi; Apri Utami Parta Santi; Rina Nuryani; Halimah Halimah; Anzily Rahma Alia; Muraina Kamilu Olanrewaju (Universitas Ahmad Dahlan, 2026)
This study aims to develop and evaluate contextual-based Indonesian language teaching materials for foreign speakers (BIPA) within the Muhammadiyah university setting. Addressing the limitations of existing culture-based materials, the study proposes an institution-based approach that integrates Muhammadiyah values, academic practices, socio-religious perspectives, and authentic campus communication contexts into instructional design. A mixed-method research design was employed within a research and development (R&D) framework guided by the ADDIE model. The study involved 15 BIPA learners, 2 instructors, and 3 experts. The needs analysis revealed that learners required instructional materials integrating linguistic, communicative, academic, socio-cultural, and institutional dimensions, with institutional context emerging as the most important component. The developed materials were validated by experts and were rated highly appropriate due to their alignment with learners’ communicative needs, authentic learning situations, and integration of institutional cultural values. The effectiveness test demonstrated a statistically significant improvement in learners’ communicative competence between the pre-test and post-test, with a large effect size indicating substantial learning gains. The findings suggest that the integration of authentic campus interactions and Muhammadiyah-based contextual content can enhance learners’ ability to communicate effectively in academic and social environments. This study contributes to BIPA pedagogy by extending contextualization beyond local cultural representation toward an institution-based framework that integrates cognitive, cultural, and contextual dimensions. The findings provide a practical model for developing context-sensitive BIPA materials in Islamic higher education institutions and other educational settings with distinctive institutional identities.